Determination of the Fraud Hexagon on the Tendency of Fraudulent Financial Reporting in the Provinces of Indonesia - Maharanti, Puan; Yudi, Yudi; Friyani, Rita (International Journal of Multidisciplinary Approach Research and Science, 2024)
Fraudulent financial reporting occurs when public officials and others intentionally engage in dishonest and illegal acts to alter or conceal financial information, thereby creating a false picture of financial health and performance. As a result, financial statements become unreliable and misleading for stakeholders when making important decisions. This study adopts the fraud hexagon which identifies six elements (pressure, capability, collusion, opportunity, rationalization, and arrogance) to analyze and obtain empirical evidence regarding the factors that influence the tendency of fraudulent financial reporting. A total of 34 provincial governments in Indonesia in 2019-2022 comprised the population and sample used in this study. Multiple linear regression data analysis techniques were used in this study to evaluate hypotheses using secondary data and SPSS 29. The results showed that the tendency of fraudulent financial reporting was simultaneously influenced by the elements of the fraud hexagon. The tendency of fraudulent financial reporting is partially influenced by pressure, opportunity and arrogance. However, the tendency of fraudulent financial reporting is partially uninfluenced by capability, collusion, and rationalization. Based on the results of this study, it is recommended that the government, society, and other stakeholders focus on key elements that affect the integrity of financial reporting.